2015
DOI: 10.1007/s00702-015-1450-0
|View full text |Cite
|
Sign up to set email alerts
|

Three novel presenilin 1 mutations marking the wide spectrum of age at onset and clinical patterns in familial Alzheimer’s disease

Abstract: Presenilin 1 (PSEN1) mutations are the major cause of autosomal dominant Alzheimer's disease (ADAD). Here we report three novel PSEN1 mutations: Ile238_Lys239insIle, Ala246Pro and Ala164Val from patients who manifested in their twenties, forties and seventies, respectively, with variant clinical presentations of dementia. These cases exemplify the tremendous heterogeneity of clinical phenotypes and age of onset associated with PSEN1 mutations. The possibility of ADAD--not previously suspected in two of our pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“… 45–50 Yes Possibly damaging via in silico. [ 19 ] Roeber et al, 2015 W165C (G > C) Not available 37–47 Yes ↑Aβ42 and ↓Aβ40; elevated Aβ42/Aβ40 ratio [ 36 ] Campion et al, 1999 W165C (G > T) EOAD, a severe form of atrophies and rapid deterioration in cerebral and cerebellar 45 Yes ↓Aβ42 and ↓Aβ40; elevated Aβ42/Aβ40 ratio [ 37 ] Syama et al, 2018 W165G Not available 34–38 Yes Not available [ 39 ] Higuchi et al, 2000 L166H MRI: hippocampal atrophy and cortical atrophy. SPECT: bilateral hypometabolism in the parietal and frontal lobes.…”
Section: Discussionmentioning
confidence: 99%
“… 45–50 Yes Possibly damaging via in silico. [ 19 ] Roeber et al, 2015 W165C (G > C) Not available 37–47 Yes ↑Aβ42 and ↓Aβ40; elevated Aβ42/Aβ40 ratio [ 36 ] Campion et al, 1999 W165C (G > T) EOAD, a severe form of atrophies and rapid deterioration in cerebral and cerebellar 45 Yes ↓Aβ42 and ↓Aβ40; elevated Aβ42/Aβ40 ratio [ 37 ] Syama et al, 2018 W165G Not available 34–38 Yes Not available [ 39 ] Higuchi et al, 2000 L166H MRI: hippocampal atrophy and cortical atrophy. SPECT: bilateral hypometabolism in the parietal and frontal lobes.…”
Section: Discussionmentioning
confidence: 99%
“…Presenilin proteins, PS1 and PS2, are constituents of the γ-secretase complex, which carry out amyloid precursor protein (APP) proteolytic processing [ 2 ]. Three new novel PS1 mutations have been uncovered in patients with a vast heterogeneity of clinical phenotypes [ 5 ]. Investigation of wild-type γ-secretase with six familial Alzheimer’s disease (FAD) mutants in PS1 and five FAD mutants in the Aβ peptide segment of the APP revealed that all mutations were associated with decreased γ-secretase activity and a reduced age of disease onset and death [ 6 ].…”
Section: γ-Secretase Activity Of Presenilinmentioning
confidence: 99%
“…The age of onset may be variable; several cases were related to a young disease onset (late twenties or early thirties), such as Leu85Pro [11], His163Pro [12] or Met233Val [13]. Meanwhile, other mutations, such as Met84Val [14] Ala164Val [15] or Phe175Ser [16], were associated with late disease onset (late sixties and seventies). In addition to the EOAD phenotypes, several different symptoms were related to PSEN1 mutations, including myoclonus, seizures, extrapyramidal symptoms, spastic paraparesis and behavioral and language dysfunctions [17][18][19].…”
Section: Introductionmentioning
confidence: 99%